In Vitro L6 Irritation Assay Predicts Clinical Injection Site Reactions for Small Molecules. (11th March 2016) - Willy, Jeffrey A.; Schulte, Nanette E.; Kreklau, Emiko L.; Walgren, Jennie L.; Renninger, Matthew L.; Baker, Thomas K.
Abstract: Injection site reactions (ISRs) are commonly encountered in the development of parenteral drugs, and severe ISRs can lead to preclinical and clinical dose limiting toxicities. Tools to assess the risk of clinical ISRs during drug development are not well established. We developed an in vitro ISR screen using L6 rat myotubes to assess compounds for irritation risk. Reference compounds that were either known to induce ISRs or were non-irritating in the clinical setting were used to validate this method. We evaluated three compounds, two with known clinical ISRs (mitoxantrone and doxorubicin) and one without clinical ISR (metoprolol), using a preclinical in vivo rat model and the L6 in vitro model at clinically relevant concentrations, and showed that the L6 assay is a better prognostic indicator for clinical ISR risk. We then utilized this assay during early preclinical development to guide optimization of structure activity relationship (SAR), selection of dose concentrations for pre-clinical in vivo experiments, and prioritization of alternative formulations to minimize ISR risk. Our studies indicate that the L6 assay is a better measure of clinical ISR risk than current in vivo preclinical models, and that it can help guide not only compound selection, but also selection of dose concentration and formulation.